CURRENT CONDITION AND PROBLEMS OF PHYSICAL CULTURE DEVELOPMENT IN UNIVERSITY - Svetlana I. Bochkaryova (Plekhanov Russian University of Economics, 2017)
The article discusses problems, which arose during designing working programs for modules on physical culture and sport according to the federal state education standard of higher education of the new generation. The authors showed important aspects fostering the development of working programs which can meet the current requirements. Figures of the survey conducted among students in order to find out their opinion about the process of physical training in university. The federal state education standard provides the opportunity to realize modules on physical culture and sport independently and it makes it possible to interpret the subject content freely. However, it could distort the target of subjects of state policy in the field of physical culture and sport.